Microplastics negatively impact embryogenesis and modulate the immune response of the marine medaka Oryzias melastigma. (September 2020) - Chen, Jin-Can; Chen, Meng-Yun; Fang, Chao; Zheng, Rong-Hui; Jiang, Yu-Lu; Zhang, Yu-Sheng; Wang, Ke-Jian; Bailey, Christyn; Segner, Helmut; Bo, Jun
Abstract: Microplastic (MP) pollution is an emerging contaminant in aquatic environments worldwide. Nonetheless, the developmental toxicity of MPs in the early life stages of fish and the mechanisms involved are not yet fully understood. The present study investigated the effects of different concentrations of polystyrene (PS) MPs on the early development of the marine model fish the medaka Oryzias melastigma . Our results showed that waterborne exposure to PS MPs significantly delayed the hatching time, altered the heartbeat and decreased the hatching rate of embryos. Furthermore, the genes involved in cardiac development, encoding for embryo-hatching enzymes, as well as inflammatory responses were significantly upregulated. The transcriptome results showed that mainly the pathways involved in metabolism, immune response, genetic information processing and diseases were significantly enriched. These results demonstrate that PS MPs negatively impact embryogenesis and the immune response of O. melastigma . Highlights: MPs significantly changed the hatching time and hatching rate of medaka embryos. MPs appeared to impair the heart development of embryos. MPs induced inflammatory and immune genes of embryos. Toxicity of MPs is size- and time-dependent.